Improvisasi Pembelajaran Pendidikan Agama Islam Pada Masa Transisi - Dinil Abrar Sulthani (Institut Agama Islam Negeri Palopo, 2020)
AbstractThis article was written to explain the importance of improvising learning during the transition period. The transition period brings changes in all lines of human life, including in the field of education. Educational institutions need to organize interesting learning and creations for students. The effort made is learning improvisation. In learning Islamic Religious Education, teachers need to improvise learning so that teaching materials are accepted by students easily. This article aims to review various improvisations that can be carried out by education providers. This thought writing uses the literature method with a qualitative descriptive analysis approach. The results of this study emphasize; 1) Islamic Religious Education means the concept of religious teachings that every student needs to learn, 2) Islamic Religious Education material should be made attractive during the transition period, and 3) Learning Islamic Religious Education requires the meaning of evaluation which is oriented towards the study and analysis of the teaching and learning process. The conclusion of this article that learning improvisation can be carried out by; 1) Packaging the material simply, 2) Providing learning feedback, and 3) Confirming the learning process of students. Keywords : Transition period, improvisation, Islamic Religious Education, Student AbstrakTulisan pikiran ini dibuat untuk menjelaskan pentingnya improvisasi pembelajaran pada masa transisi. Masa transisi membawa pengaruh perubahan bagi semua lini kehidupan manusia, termasuk dalam bidang pendidikan. Lembaga pendidikan perlu menyelenggarakan pembelajaran yang menarik dan kreasi bagi peserta didik. Upaya yang dilakukan adalah improvisasi pembelajaran. Dalam pembelajaran Pendidikan Agama Islam, guru perlu melakukan improvisasi pembelajaran agar materi ajar diterima peserta didik dengan mudah. Tulisan ini bertujuan untuk mengulas berbagai improvisasi yang dapat dilaksanakan oleh penyelenggara pendidikan. Tulisan pikiran ini menggunakan metode kepustakaan dengan pendekatan kualitatif analisis deskripsi. Hasil dari kajian ini menekankan pada; 1)Pendidikan Agama Islam bermakna pada konsep ajaran agama yang perlu dipelajari oleh setiap peserta didik, 2)Materi Pendidikan Agama Islam hendaknya dibuat menarik pada masa transisi, dan 3)Pembelajaran Pendidikan Agama Islam mensyaratkan makna evaluasi yang berorientasi pada kajian dan analisis dari proses belajar mengajar. Kesimpulan tulisan ini improvisasi pembelajaran dapat dilaksanakan dengan; 1)Mengemas materi dengan sederhana, 2)Memberikan feed-back pembelajaran, dan 3) Mengonfirmasi proses belajar mengajar peserta didik. Kata Kunci : Masa transisi, Improvisasi, Pendidikan Agama Islam, Peserta didik